The complete mitochondrial genome of Pseudoxenodon macrops - Hao Zong; Tianmeng Zhao; Tao Hu; Dan Feng; Jialing Li; Rong Du; Changkun Fu (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we obtained the complete mitochondrial genome of Pseudoxenodon macrops. The sequenced mitogenome is 20,978 base pairs(bp) in length, which contained 13 protein-coding genes (PCGS), 22 transfer RNA genes (tRNA), 2 Ribosomal RNA genes (rRNA) and 2 control regions (D-loop). The total base composition of mitochondrial DNA is that A, C, G and T occupied 33.1%, 26.6%, 12.8% and 26.5%, respectively. The mitochondrial genome of Pseudoxenodon macrops will help us reveal phylogenetic relationships among the species of the Colubridae family.